Integrating Islamic Values into Accounting Education: Toward a Conceptual Model of Character Development and Ethical Accountability - Sri Rosmalina Soejono; Sarlina Sari; Iswadi; Nur Indah Yusari (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The increasing demand for ethically responsible accounting professionals has highlighted the importance of integrating moral and spiritual values into accounting education. Although previous studies have emphasized ethics education and Islamic accounting awareness, empirical evidence explaining how the integration of Islamic values contributes to students’ character development within accounting learning remains limited. This study aims to explore the role of Islamic value integration in strengthening students’ Islamic character and to identify the challenges and strategies associated with its implementation in accounting education. An exploratory qualitative design was employed involving 15 participants consisting of accounting lecturers, final-year accounting students, and accounting practitioners. Data were collected through semi-structured interviews and analyzed using thematic analysis supported by NVivo software. The findings revealed four core Islamic values underpinning accounting learning and practice, namely amanah (trustworthiness), sidq (honesty), adl (justice), and ihsan (professional excellence). These values were integrated into learning through Quran–Hadith contextualization, ethical reflection, and case-based learning, contributing to the development of ethical responsibility, integrity, and ethical sensitivity among students. The study also identified several implementation challenges, including limited Islamic-based teaching materials, insufficient lecturer preparedness, and the absence of systematic curriculum guidelines. Furthermore, a conceptual model linking Islamic values, learning integration processes, and character development outcomes was developed. This study contributes to the accounting education literature by extending ethics education beyond predominantly secular frameworks and introducing a spiritually grounded perspective on character formation. The findings provide practical implications for curriculum development and support the design of more holistic accounting education that integrates technical competence, ethical accountability, and spiritual responsibility.